Delayed second polar body extrusion increases abnormal cleavage risk and impairs embryonic developmental potential: a retrospective time-lapse study - Haifang Liu; Shikai Wang; Xianbao Mao; Jie Qin; Yongyi Pan; Zhengda Li; Xiaohui Zhang; Pingpin Wei; Liangshi Chen; Yueyue Huang; Wen Shi; Liling Liu; et al. (Scientific Reports)
Abstract The purpose of this study was to elucidate the effect of second polar body (Pb2) extrusion time on dynamic cleavage parameters and embryonic developmental potential. Data on a total of 398 cycles from patients who underwent intracytoplasmic sperm injection (ICSI) treatment between September 2021 and May 2023 were retrospectively analysed. Our results revealed that the average Pb2 extrusion time after ICSI was 3.13 ± 1.63 h and was negatively correlated with Day3 high-quality embryos (odds ratio [OR] = 0.857, CI: 0.810–0.907, P < 0.001) and the blastocyst formation (OR = 0.806, CI: 0.752–0.864, P < 0.001) and high-quality blastocyst formation (OR = 0.755, CI: 0.669–0.851, P < 0.001) but was positively associated with direct cleavage (DC) (OR = 1.081, CI: 1.026–1.139, P = 0.004) and chaotic cleavage (CC) (OR = 1.148, CI: 1.081–1.220, P < 0.001). The Day3 high-quality embryo rate and blastocyst formation rate and high-quality blastocyst formation rate of the > 5 h group were significantly lower than those of the 0–3 h, > 3–4 h and > 4–5 h groups (P < 0.05), while the percentages of DC and CC in the > 5 h group were significantly greater than those in the 0–3 h group (P < 0.05). As the Pb2 extrusion time increased, other embryonic development parameters also significantly increased, including time to pronuclear appearance (r = 0.697, P < 0.001), time to pronuclear fading (r = 0.291, P < 0.001), time to the two cells (r = 0.306, P < 0.001), time to the four cells (r = 0.203, P < 0.001), time to the eight cells (r = 0.138, P < 0.001), time to full blastocyst formation (r = 0.128, P < 0.001), and duration of the time period from three cells to four cells (r = 0.076, P < 0.001). The results of fresh embryo transfer revealed that the clinical pregnancy rate (CPR) and implantation rate (IR) were significantly lower in the Pb2 extrusion delay group than in the Pb2 extrusion normal group (P < 0.05). Overall, delayed Pb2 extrusion was significantly associated with reduced embryonic developmental efficiency, which may be due to a slower speed of development and a significant increase in the incidence of abnormal cleavage. Moreover, transfer of embryos with delayed Pb2 extrusion may impair pregnancy outcomes.